Effect of dynamic plastic deformation on microstructure and annealing behaviour of modified 9Cr−1Mo steel. (April 2015) - Zhang, Z. B.; Mishin, O. V.; Tao, N. R.; Pantleon, W.
<x content-type="archive" xml:space="preserve">Abstract</x> The effect of dynamic plastic deformation on the microstructure of a modified 9Cr−1Mo steel has been investigated in comparison with the effect of quasi-static compression. It is found that the boundary spacing after dynamic plastic deformation is smaller and the hardness is higher than those after quasi-static compression. The microstructure after dynamic plastic deformation is however less stable than the microstructure after quasi-static compression. Annealing at 675 and 700°C leads to structural coarsening and recrystallisation in each sample, but with recrystallisation occurring faster in the sample annealed after dynamic plastic deformation. The lower thermal stability of the microstructure produced by dynamic plastic deformation is attributed to a higher driving force for recrystallisation in the dynamically deformed material.